Influence of Work Environment and Work Motivation on Employee Performance at CV Britanindo Bandung - Putri, Ratna Komala; Priansa, Donni Juni (Universitas Proklamasi 45, 2023)
This research aims to ascertain the work environment, work motivation, and employee performance at CV Britanindo Bandung and to find out how much influence the work environment, work motivation, and employee performance at CV Britanindo Bandung. Since the location is in an industrial area, where the weather is quite hot and there is a high risk of air pollution that can cause illness for employees, CV Britanindo is considered to be inappropriate. The work motivation of the employees at CV Britanindo Bandung tends to be low since the employees get a work environment that follows the amount of production that can be generated and the income earned by the company, so employees feel unmotivated to work. It impacts the achievement of production produced by employees who cannot achieve production targets properly. The research method used is descriptive-verificative. The sample used in this study was all employees of CV Britanindo Bandung. Data processing is conducted using multiple linear regressions, analysis of the coefficient of determination, and hypothesis testing. Based on the results of the study, it can be concluded that influence does emerge in the work environment on employee performance at CV Britanindo Bandung and there is an influence between work motivations on employee performance at CV Britanindo Bandung; and there is a mutual influence between work environment and work motivation on employee performance at CV Britanindo Bandung.